INOVASI PRODUK SABUN HERBAL TRANSPARAN MENGGUNAKAN METODE MICROWAVE DARI LIMBAH PALA - Kapelle I.B.D; M. Syamsul Maarif; Yandra Arkeman (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2014)
Nutmeg oil production generates waste in the form of residue distillation are containingcompound trimeristin. Innovation in the waste utilization by producing transparent herbal soapsusing the microwave method for the transesterification process. The production process usesmicrowave method requires a short time, costs and energy are small and good quality is a strength indeveloping product . This product has a market opportunity because it can compete with otherproducts, the advantages that are the effects of aromatherapy herbal ingredients.